THU0270 European ankylosing spondylitis (AS) infliximab cohort (EASIC) long-term extension: Efficacy and safety of infliximab over a time period of more than 7 years in patients with AS. (23rd January 2014) - Heldmann, F.; Baraliakos, X.; Brandt, J.; van der Horst-Bruinsma, I.; Landewé, R.; Sieper, J.; Burmester, G.R.; van den Bosch, F.; de Vlam, K.; Gaston, H.; Grünke, M.; Appelboom, T.; et al.
Abstract : Background: The knowledge on the long term efficacy and safety of anti-TNF therapy in patients with AS is rather limited. Methods: 71/81 patients (87.7%) who completed the 2 year (y) EASIC trial (after 2y of ASSERT and 1.3y between trials) were directly included into the EASIC extension for another 96 weeks. 10/81 patients had discontinued for logistic reasons. All patients received infliximab in the same dosage regime as in the EASIC core study (5mg/kg every 6-8 weeks). The patients received a total treatment period of more than 7y. All adverse events (AE), serious adverse events (SAE) and drop-outs were recorded similar to common efficacy indices (BASDAI, BASFI, Enthesitis index, CRP) which were available for 64 completers and 6 patients with premature withdrawal. Results: 64 (90.1%) of patients completed the trial, while 7 did not. 3 were discontinued by the investigator (1 due to loss of response, infections and basal cell carcinoma, respectively), 1 was lost to follow-up and 3 withdrew consent. The mean BASDAI for completers was 2.4 (±1.7) with 49/64 (76.6%) showing BASDAI levels <4, and 42 (65.6%) even showed a BASDAI <3, indicative of low disease activity. Half of the 6 patients with withdrawal showed BASDAI levels >4 at their last visit. The mean CRP for completers (n=61) was 4.9±5.9 mg/l at the last study visit. 81% of patients showed no enthesitis. The mean BASFI of 64 completers was 3.1±2. In the extension 476 AE occurred in 63/71 patients (88.7%), 61 of which (96.8%) had >1 AE. There were 13 SAE during the whole study period. The most common AE were infections (35.1% of all AE): 116 (69.5%) of the respiratory tract, 25 (14.9%) of the skin, 12 (7.2%) of the gastrointestinal and 7 (4.2%) of the urogenital tract. Two malignancies were observed: one basal cell carcinoma of the skin (patient was discontinued), while the other patient refused to discontinue despite a diagnosis of skin melanoma because of the favourable effect of infliximab. These 2 SAE were the only SAE that were judged to be possibly related to infliximab. 5 minor infusion reactions were observed in 5 patients, 3 of whom completed the trial. Other AEs were: 1 herpes zoster, 7 cases of elevated liver enzymes in 6 patients, 36 non-infectious AE of the skin (5 cases of psoriasis), 3 flares of inflammatory bowel disease in 2 patients, 2 episodes of anterior uveitis (1 flare of a patient with recurrent uveitis and one new onset). Conclusions: Treatment with infliximab was efficacious and safe with a favorable benefit-risk ratio for patients with AS for >7 years. The most AE were infections. There were no serious infections or deaths. The 2 cases of skin malignancy are in line with previous study results and reports from other registries. Disclosure of Interest: None Declared